Legal Protection for Consumers in the Distribution of Illegal Gadgets - Hadziqotun Nahdliyah; Isniyatin Faizah; Suisno; Moh. Fatih Taqiyuddin (Universitas Islam Lamongan, 2025)
Technological developments and the high demand for gadgets have led to the widespread distribution of products that do not comply with legal requirements, particularly those related to customs. The distribution of gadgets without official customs documents not only harms the state in terms of tax revenue but also causes losses for consumers. This study aims to analyze the form of legal protection for consumers who purchase illegal gadgets without knowing their legal status, as well as examine the government's role in combating the circulation of these products. The research method used is normative juridical with a statutory regulatory approach. The results show that consumers have the right to security, comfort, and correct information as stipulated in Law Number 8 of 1999 concerning Consumer Protection. However, weak supervision and a lack of legal literacy make consumers vulnerable to becoming victims. Therefore, it is necessary to strengthen regulations, increase supervision of product distribution, and educate the public so that consumer rights are optimally protected